Adaptasi Tanaman Indigofera zollingeriana (Miquel 1855) (Leguminosae : Indigofereae) pada Berbagai Tingkat Naungan - Saijo Saijo; . Sudradjat; Sudirman Yahya; Yayat Hidayat (Institut Pertanian Bogor, 2018)
Indigofera zollingeriana is a bush type legume plant that grows well in full light but tolerant to shade conditions. Modification efforts of the environment with paranet shade treatment are the accurate approach. The objective of this research was to study the tolerance limit of I. zollingeriana plant at various shade levels. The study was conducted in October 2016-April 2017 at the Leuwikopo-IPB Bogor and used randomized block design with one shade factor (0, 40, 65, and 80%). The results of the measurement of microclimate with various shading levels showed that in the shade treatment 40%, the intensity of light decreased by 40% the temperature decreased by 6%, while the humidity increased by 10%. In the 65% shade, the light intensity decreased by 62%, the temperature decreased by 10%, while the humidity increased by 24%. In the 80% shade, the light intensity decreases 95%, the temperature decreases 13%, while the humidity increases 34%. The shade intensity has a real significant on decreasing stem diameter, number of branches, canopy dry weight, and roots. I. zollingeriana is rather tolerant of shade and it is able to adapt to shade up to 40%.